2023
DOI: 10.1177/24730114231156422
|View full text |Cite
|
Sign up to set email alerts
|

Transportal Tibiotalocalcaneal Nail Ankle Arthrodesis: A Systematic Review of Initial Series

Abstract: Background: There is currently a scarcity of information and consensus for transportal (arthroscopic or fluoroscopic) joint preparation during tibiotalocalcaneal (TTC) fusion, and therefore this review aims to summarize the available techniques and to evaluate the outcomes after this procedure. Methods: A systematic electronic search of MEDLINE, EMBASE, and Web of Science was performed for all English-language studies published from their inception to April 4, 2022. All articles addressing arthroscopy in TTC n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The authors highlighted that if arthroscopic preparation is undertaken, accessory portals may be required to ensure adequate joint preparation. Other studies have found high fusion rates with minimally invasive 22 and arthroscopic 23,24 hindfoot joint preparation for TTC nailing, suggesting these approaches are an alternative when open joint preparation is less favorable.…”
Section: Discussionmentioning
confidence: 99%
“…The authors highlighted that if arthroscopic preparation is undertaken, accessory portals may be required to ensure adequate joint preparation. Other studies have found high fusion rates with minimally invasive 22 and arthroscopic 23,24 hindfoot joint preparation for TTC nailing, suggesting these approaches are an alternative when open joint preparation is less favorable.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there have been few studies on TTCA with arthroscopic-assisted hindfoot nailing, with varying limitations, and a recent review attempted to report general results [26]. After examining the data of 65 patients in five studies, a significant increase in clinical scores was observed, with a major complication rate of 13.8%.…”
Section: Comparisons Of Applicable Implants Inmentioning
confidence: 99%